Vitamin D : Volume 2: Health, Disease and Therapeutics. - Feldman, David (ClinicalKey., 2017)
Vitamin D: Volume 2: Health, Disease and Therapeutics, Fourth Edition, authoritatively covers the evidence for new roles for vitamin D, ranging from cardiovascular disease, to cancer, diabetes, inflammatory bowel disease, multiple sclerosis and renal disease. This collection represents a who's who of vitamin D research and the coverage is appropriately broad, drawing in internal medicine, orthopedics, oncology and immunology. Clinical researchers will gain a strong understanding of the molecular basis for a particular area of focus. -- Publisher.